Association between contraceptive use and intimate partner violence against peruvian women in reproductive age - Quispe-Apolinario, Rocio (2020)
Introduction. Intimate partner violence against women is a global health problem of epidemic proportion. Objectives. Establish the association between contraception use and intimate partner violence against women of reproductive age in Peru. Methods. Analytical cross-sectional study of the 2017 Demographic and Family Health Survey. The association was established based on the complete surveys. Bivariate and adjusted prevalence ratios (PRa) of having suffered intimate partner violence and contraceptive use were estimated. Results. Data from 21 392 women were analyzed, 10,6% suffered intimate partner violence, 10% used contraceptives, 14,8% was between 15 and 24 years old, 11,7% completed primary education, 12,8% lived in the highlands. In the adjusted prevalence ratio, the use of modern contraception was related to a decreased likelihood of intimate partner violence compared with non-use. Conclusions. The use of modern contraception was related to a decreased likelihood of intimate partner violence.